Performance enhancement of horizontal extension and thermal energy storage to an abandoned exploitation well and satellite LNG station integrated ORC system. (September 2022) - Xiao, Fei; Yang, Lizhong; He, Lei; Gil, Antoni; Rajoo, Srithar; Zhao, Zhiye; Romagnoli, Alessandro; Cabeza, Luisa F.
Graphical abstract: Highlights: Combined LNG cold to utilize the low-grade heat from abandoned exploitation wells. Included the horizontal extension in the well heat exchanger model to extract higher grade heat. Analyzed the influence of various well parameters and working conditions. Designed thermal energy storage systems for the varying energy supply profiles. Demonstrated thermal energy storage can increase the off-design power production. Abstract: Tens of millions of abandoned exploitation wells (AEW) exist throughout the world, posing a threat to the environment and costing extra investment for decommissioning. Revitalization of the AEW offers a cost-effective solution for geothermal energy exploitation by saving the high costs of decommissioning and drilling. However, the thermal resources from AEW are usually of low and medium grade. Measures should be taken to increase the efficiency of AEW geothermal power plants. Meanwhile, the regasification process of satellite liquified natural gas (LNG) stations worldwide suffer from a loss of high-grade cold energy. Various studies have used geothermal heat and LNG cold to produce electricity, yet the horizontal extension of the AEW that may increase the recovered temperature, and the fluctuation of the LNG flow that may reduce the power output, were not discussed. This study proposes and evaluates a novel integrated organic Rankine cycle (ORC) system that uses the geothermal heat from the AEWs and waste LNG cold energy from satellite LNG stations, focusing on the performance enhancement of horizontal extension to increase the geothermal temperature and thermal energy storage to stabilize the LNG cold energy supply. A numerical model is developed that considers the horizontal extension in the AEW, and the horizontal extension is found to significantly increase the geothermal fluid temperature. A machine learning-based predictive model is built to assess the AEW outlet temperature under given parameters and working conditions. Cold thermal energy storage (CTES) modules are designed and optimized to stabilize the waste cold energy recovery when exposed to highly fluctuating LNG supply during off-design operation. CTES increased the ORC efficiency by 38.5% and has the potential to significantly shorten the payback period. Therefore, by utilizing the horizontal extension of the AEW and combining the power generation with LNG cold through thermal energy storage, the zero-emission geothermal and waste cold energy-based system can be a viable solution for future AEW revitalization and LNG waste cold energy utilization.